Relationship between the Accuracy of Diagnosis and Action Codes with Pending BPJS Claims for Inpatients at Idaman Banjarbaru Hospital - Lutfia, Hikmatul; Restu, Melinda; Wardhani, Annalia (Universitas Bondowoso, 2024)
ABSTRACT Background: Hospital claims are bills in the form of fees for services that have been provided to insurance participant patients, in this case BPJS Health. If the file verification process is not correct in its coding, it results in pending BPJS claims to health facilities. The purpose of this study was to determine the relationship between the accuracy of diagnosis and action codes with pending claims for inpatients at Idaman Banjarbaru Hospital. Method: The research design used quantitative research methods with a cross-sectional approach using a checklist sheet instrument. The population amounted to 3,964 inpatient claim submission files from January to March 2024. The sample of this study amounted to 363 files with random sampling technique. Data analysis used univariate and bivariate analysis. Results: The results of this study found that 69 (19%) claim files were pending and 294 (81%) were not pending, while the diagnosis and action codes were correct 344 (94%) and inappropriate 19 (8.3%). The Chi Square test analysis value with a p-value of 0.001 < α 0.05 means that there is a relationship between the accuracy of diagnosis and action codes with pending BPJS claims for inpatients at Idaman Banjarbaru Hospital. Conclusion: Idaman General Hospital needs to hold socialization, evaluation meetings, training and making written SOPs with coding officers with doctors and BPJS verifiers so that there is no pending claim payment process by the JKN team.